Reliability of Roentgenographic Knee Alignment Measurements in Gonarthrosis - Huang, Teng-Le; Wang, Chen-Chie; Yang, Kai-Chiang; Wu, Chang-Chin (The Journal of Knee Surgery, 2018)
A reliable method of measuring knee alignment is critical in the preoperative planning of high tibial osteotomy (HTO). This radiological study, based on the measurements of the mechanical and anatomical axes of the lower limb, aimed to determine which method would be more reliable and reproducible. From 2004 to 2013, 50 consecutive patients (50 knees) with medial gonarthrosis were treated with valgus-producing HTO. Four independent investigators assessed preoperative standing lower limb radiography (including hip, knee, and ankle joints) to measure both anatomical and mechanical axes. We defined a response as a difference in the angle measured by the same investigator using the same method. The covariates were the investigators and methods. To account for both inter- and intraobserver variabilities, all data were evaluated using a generalized estimating equation model. The results revealed that the effect of the investigators was not statistically significant; however, the effect of the measurement method was highly significant (p < 0.0001). The estimated coefficient of the anatomical axis method was negative, indicating that the reproducibility of the anatomical axis method was better than that of the mechanical axis.
Keywords: tibial osteotomy; anatomical axis; mechanical axis; reproducibility